1990
DOI: 10.1007/bf02072057
|View full text |Cite
|
Sign up to set email alerts
|

Transient cholestatic hepatitis in a neonate associated with carbamazepine exposure during pregnancy and breast-feeding

Abstract: We report a 3-week-old boy with cholestatic hepatitis, most likely due to carbamazepine exposure during pregnancy and breastfeeding. Cholestasis resolved after cessation of nursing. Liver function test results and histological findings were compatible with a drug-induced hepatitis. Other causes were excluded. While carbamazepine-induced hepatitis is well known in children and adults, it has never been described in association with prenatal exposure and/or breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 7 publications
1
26
0
4
Order By: Relevance
“…The majority of patients experienced no adverse effects. The experience of Taddio et al4 with 11 infants is especially reassuring; these authors showed that despite the presence of drug in the breast milk, no adverse effects were noted. However, the presence of significant infant serum concentrations and colic5 and irritability5'6 calls for caution in using this medication in a lactating woman.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The majority of patients experienced no adverse effects. The experience of Taddio et al4 with 11 infants is especially reassuring; these authors showed that despite the presence of drug in the breast milk, no adverse effects were noted. However, the presence of significant infant serum concentrations and colic5 and irritability5'6 calls for caution in using this medication in a lactating woman.…”
Section: Discussionmentioning
confidence: 90%
“…No further episodes occurred until 51/2 months, when the baby had peripheral cyanosis lasting[10][11][12][13][14][15] minutes and affecting the lips, up-…”
mentioning
confidence: 99%
“…Nevertheless, the drug is considered compatible with breastfeeding [7,22]–[25]. In fact, it is administered, with a good safety profile, directly to patients of pediatric age.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3,8,[31][32][33][34][35][36][37][38][39][42][43][44][45][47][48][49][50][51][52]68,69] There are few published case reports describing adverse events for carbamazepine in the breast-fed infant. Frey et al [70] reported a transient cholestatic jaundice in association with maternal carbamazepine treatment during pregnancy and lactation. Cholestasis resolved after cessation of breast feeding.…”
Section: Carbamazepinementioning
confidence: 98%